Analysis of smart specialization in European regions using fuzzy classification - Markowska, Małgorzata; Kusterka-Jefmańska, Marta; Jefmański, Bartłomiej (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
The major areas of specialization assessment cover for example export, R&D expenditure, employment rate, high-tech products (e.g. patents). Many measures indicated in the subject literature for specified areas cannot be currently determined at regional level due to data unavailability. The article attempts to identify the areas and directions of changes in the smart specialization development of the European regions. An analytical approach, based on the application of fuzzy classification in the analysis of dynamic data, was used for this purpose. The analysis covered 265 European regions at NUTS 2 level, described by variables characterizing employment shares in economic sectors. The level of membership to the separated classes was estimated for each region in particular years of the adopted research period 2000–2010, which facilitated analyzing the directions of their location changes in the European area divided into classes. The obtained results allowed for the positive verification of the proposed hypotheses about the usefulness of fuzzy classification in the identification of areas and directions for smart specialization changes in regions establishing the European regional area. Both, the regions characterized by the changing sector system and the onesmaintaining their sector specialization profiles in the adopted research period, were identified in the course of the conducted analyses.
Argumenta Oeconomica, 2016, Nr 2 (37), s. 31-65
Keywords: fuzzy classification; smart specialization; NUTS 2 regions